Pengaruh Pemberian Sari Kurma dan Madu terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Trimester III di Puskesmas Bangetayu Kota Semarang - Rahmawati, Alfiah; Eka Dewi Setianing Tiyas; Arum Meiranny (Sultan Agung Islamic University of Semarang, 2024)
Anemia is one indicator of the cause of AKI which is caused by the number of red blood cells in the body is still too little so that the body lacks hemoglobin. The purpose of the study was to determine whether there was an effect of giving date palm juice and honey to the increase in Hb levels of pregnant women in the third trimester at Bangetayu Health Center Semarang City. The research design was pretest-posttest with control group design, with a sample of 30 respondents to determine the effect of treatment on the intervention group by comparing with the control group. The results showed that there was a significant effect between the consumption of date palm juice and honey on the incidence of anemia in pregnant women TM III at Bangetayu Health Center Semarang City with p = 0.002 < = 0.05. The results of the RR value are 3.14, which means that respondents who do not consume date palm juice and honey have a 3.14 times possibility of experiencing anemia compared to those who consume date palm juice and honey.